2018
DOI: 10.1016/j.jchromb.2018.04.036
|View full text |Cite
|
Sign up to set email alerts
|

The enrichment of chlorogenic acid from Eucommia ulmoides leaves extract by mesoporous carbons

Abstract: Herein, we report an efficient separation and enrichment method for chlorogenic acid from crude extracts of Eucommia ulmoides leaves using carbon adsorbents. The effects of the pore structure of the carbon adsorbents on the adsorption capacity were studied. Of the four adsorbents investigated, mesoporous carbon (MC3) showed the highest adsorption capacity (294 mg/g of carbon) for chlorogenic acid due to its high mesopore volume. The static adsorption of CGA on carbon can be accurately described using the Freun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Therefore, CNPC1 could have a strong adsorption effect on active substances such as PMFs during the enrichment process. Similarly, an enrichment method for CGA using mesoporous carbon has been developed by Qin et al [ 28 ]. The mesopore volume of the carbon adsorbents was found to significantly influence the adsorption capacity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, CNPC1 could have a strong adsorption effect on active substances such as PMFs during the enrichment process. Similarly, an enrichment method for CGA using mesoporous carbon has been developed by Qin et al [ 28 ]. The mesopore volume of the carbon adsorbents was found to significantly influence the adsorption capacity.…”
Section: Resultsmentioning
confidence: 99%
“…GAs as adsorbents have shown their versatility as pollutant absorbers for the removal of dyes, formaldehyde, and other environmental toxins; on membranes for separating oil-in-water emulsion; and for efficient food toxin removal [ 22 , 23 ]. AC is often used as an adsorbent to remove dark-colored compounds [ 24 ], heavy metals [ 25 ], pesticides [ 26 ], and some organic acids [ 27 , 28 ], but few reports exist on the use of AC to enrich PMFs from CPW. In the adsorption process of AC, it is simpler and less time-consuming when compared to other methods.…”
Section: Introductionmentioning
confidence: 99%
“…It is synthesized by the condensation of caffeic acid and quinic acid 21 . CA is an important active component in many edible plants and medicinal plants, which is widely distributed in plants, from high dicotyledons to ferns, but there are few plants with high content 22 . CA is mainly in the plant family of Eucommia, Lonicerae and Artemisia, including eucommia, honeysuckle, artemisia, artemisia sunflowers, relay flowers, coffee and cocoa trees 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its unique and tunable pore structures, high surface areas and mechanical stability, mesoporous carbons (pore size between 2 and 50 nm) have been proven to be a kind of efficient adsorbents for adsorptive natural products. The study shown that mesoporous carbons were more suitable for adsorbing macromolecules, such as mesoporous carbons have been used by Qin et al to enrichment of chlorogenic acid from eucommia ulmoides leaves (Qin et al, 2018). Li et al synthesized two mesoporous carbons via a hydrothermal treatment approach, and evaluated adsorption performance of two mesoporous carbons for berberine hydrochloride and matrine from water (Li et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%